2018
DOI: 10.1126/scitranslmed.aao2565
|View full text |Cite|
|
Sign up to set email alerts
|

The ERBB network facilitates KRAS-driven lung tumorigenesis

Abstract: KRAS is the most frequently mutated driver oncogene in human adenocarcinoma of the lung. There are presently no clinically proven strategies for treatment of KRAS-driven lung cancer. Activating mutations in KRAS are thought to confer independence from upstream signaling; however, recent data suggest that this independence may not be absolute. We show that initiation and progression of KRAS-driven lung tumors require input from ERBB family receptor tyrosine kinases (RTKs): Multiple ERBB RTKs are expressed and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 45 publications
10
76
0
Order By: Relevance
“…2D). Moreover, we observed increased protein levels of total RAS in RAS mutant organoids, indicative of positive feedback regulation induced by oncogenic RAS proteins as previously reported [53][54][55] .…”
Section: Generation Of Endogenous Oncogenic Ras and Braf Knock-in Varsupporting
confidence: 88%
“…2D). Moreover, we observed increased protein levels of total RAS in RAS mutant organoids, indicative of positive feedback regulation induced by oncogenic RAS proteins as previously reported [53][54][55] .…”
Section: Generation Of Endogenous Oncogenic Ras and Braf Knock-in Varsupporting
confidence: 88%
“…In both types of tumor cell neratinib reduced the expression of K-RAS. Others have also recently shown that neratinib and afatinib in solid tumor cell lines can reduce ERBB1/2/3 expression [24,25].…”
Section: Discussionmentioning
confidence: 96%
“…Inhibition of single downstream effector molecules (e.g., RAF, MEK, or PI3K) did not produce major clinical benefits, where induction of compensatory mechanisms that reactivate the pathway or even activation of alternative KRAS signaling effectors may account for resistance mechanisms [10,11]. Nevertheless, since mutant KRAS cells seem to show increased dependence on receptor tyrosine kinase (RTK) signaling such as erythroblastic leukemia viral oncogene (ERBB) family, hepatocyte growth factor receptor (MET) and insulin growth factor receptor (IGFR), combined inhibition of specific signaling effectors and RTK (e.g., MEK and IGFR inhibition, or MEK and pan-ERBB inhibitors) have shown therapeutic potential [12][13][14].…”
Section: Introductionmentioning
confidence: 99%